PERLINDUNGAN HUKUM YANG IDEAL BAGI PEKERJA RUMAH TANGGA DI MASA DEPAN MELALUI PERJANJIAN KERJA (Studi Kasus Dki Jakarta) - Asma’ul Khusnaeny (Program Magister Ilmu Hukum Universitas Pancasila, 2019)
According of data that generally of dometic workers in Special Capital Region of Jakarta made oral employment agreement while amount of domestic workers and employers made written employment agreement the least. Domestic workers who made written employment agreement face the violated on the rights of worker, violation, moreover dometic workers who made oral employment agreement also weak before the law. Employers easily commit arbitrary actions that result in the detriment of domestic workers. The provisions of existing legislation have not specifically and comprehensively regulated the protection of domestic workers law. While the responsibility of the Government until the Rukun Tetangga device has not fully carried out its duties, especially in conducting guidance and supervision of domestic workers based on Regulation of the Minister of Manpower No. 2 Year 2015 on Protection of Domestic Workers. The absence of specific statutory provisions leads domestic workers to lack legal protection, there is no standard ideal written employment agreement in accordance with the conditions of decent work of domestic workers and not the maximum responsibility of the Government to Rukun Tetangga in providing legal protection, especially in the case of employment agreements. This research method is normative juridical.